Perancangan Aula Sebagai Ruang Pusat Komunikasi Santri Melalui Pendekatan Aspek Akustik di Pesantren Darul Aman Gombara Makassar - Muhammad Taufik Ishak; Baharuddin Hamzah; Rosady Mulyadi; Nurul Jamala; Asniawaty Kusno; Yusaumi Ramadhanti Fitri Taufik (Faculty of Engineering UNHAS, 2022)
One type of education in Indonesia is formal education which is supported by additional programs in the religion field. This education is generally implemented with a system of student living in dormitory that follows the provisions and supervision by the administrator. One of them is the Darul Aman Gombara Islamic Boarding School in Makassar. This Islamic boarding school area does not yet have the necessary facilities as a communication space or gathering for all student and supports student’s activities in various talents in the sport filed. The purpose of this service activity is to redesign the dormitory into a hall while maintaining the identity of the Islamic boarding school, process needs and make land available efficiently, as well as implement design ideas/concepts through an acoustic approach that is able to achieve the desired function, namely as a communication center. The method used are a discussion of the Islamic boarding school needs and present the design concepts offered, as well as direction and assistance from the results of the designs that have been designed. The result of this activity is the design of the hall as a student communication space through an acoustic aspect approach.